2018
DOI: 10.1038/s41598-018-34646-7
|View full text |Cite
|
Sign up to set email alerts
|

A bacteria-derived tail anchor localizes to peroxisomes in yeast and mammalian cells

Abstract: Prokaryotes can provide new genetic information to eukaryotes by horizontal gene transfer (HGT), and such transfers are likely to have been particularly consequential in the era of eukaryogenesis. Since eukaryotes are highly compartmentalized, it is worthwhile to consider the mechanisms by which newly transferred proteins might reach diverse organellar destinations. Toward this goal, we have focused our attention upon the behavior of bacteria-derived tail anchors (TAs) expressed in the eukaryote Saccharomyces … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…YgiM, an inner membrane protein, was firstly reported in E. coli, and it was confirmed to be anchored to peroxisomes in yeast and mammalian cells (Maddalo et al, 2011;Lutfullahoglu-Bal et al, 2018). Through homology alignment, we found a homologous gene vk055_4013 with 83% high similarity to ygiM in the genome of K. pneumoniae ATCC 43816.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…YgiM, an inner membrane protein, was firstly reported in E. coli, and it was confirmed to be anchored to peroxisomes in yeast and mammalian cells (Maddalo et al, 2011;Lutfullahoglu-Bal et al, 2018). Through homology alignment, we found a homologous gene vk055_4013 with 83% high similarity to ygiM in the genome of K. pneumoniae ATCC 43816.…”
Section: Introductionmentioning
confidence: 74%
“…Studies have shown that K. pneumoniae is the major pathogen causing localized infections such as pneumonia and liver abscesses, and disseminated infections that can lead to severe sepsis (Chew, Lin, and Teo 2017). In K. pneumoniae, the inner membrane protein YgiM has been shown to play an important role by localizing peroxisomes in yeast and mammalian cells (Lutfullahoglu-Bal et al, 2018). The present study explored whether YgiM protein deficiency affects the process of K. pneumoniae interfering with the host, and revealed a membrane associated ceRNAs network of YgiM protein in K. pneumoniae induced sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, direct dislocation and subsequent insertion into peroxisomes may occur. The ATPase Spf1 is involved in dislocation of TA proteins from the ER and in peroxisome biogenesis and function [16,[58][59][60]. To test whether this protein is required for sorting of Pex15 from the ER to peroxisomes, we analyzed the localization of Pex15 fused to the bright fluorescent protein mNeonGreen in Δspf1 cells.…”
Section: Plos Biologymentioning
confidence: 99%
“…To test whether peroxisomal TA proteins insert into the ER on their way to peroxisomes, we used a previously described model protein YgiM(TA), a bacterial derived sequence, shown to specifically target peroxisomes in mammalian cells [20]. As a reporter for protein entry into the ER we used opsin glycosylation tag (OPG) since it contains a glycosylation site which accepts glycans if exposed to the ER lumen [21].…”
Section: Exogenous Peroxisomal Ta Protein Does Not Transit Through Th...mentioning
confidence: 99%